Mengidentifikasi Tantangan yang Dihadapi Perusahaan dalam Pengimplementasian Aspek Sosial pada Prinsip ESG (Environtmental, Social, and Governance) - Aghnia Rahma Fauziah; Diva Yulianita; Pradita Salsabila Nurhasanah; Ida Farida Adi Prawira (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
As global attention to sustainability increases, the implementation of Environmental, Social, and Governance (ESG) principles has become increasingly important in the business world. However, the social aspect of ESG is often overlooked compared to environmental and governance aspects. This study aims to identify and analyze the challenges faced by companies in implementing the social aspect of ESG through a literature review of various academic sources. The findings indicate that companies encounter challenges such as limited understanding, resource constraints, organizational cultural barriers, regulatory uncertainty, and stakeholder pressure. This research provides insights into the obstacles and potential strategies that companies can adopt to address them. However, the study is limited by its reliance on literature alone, highlighting the need for future research using primary quantitative or qualitative data to strengthen these findings.